THE DEVELOPMENT OF ESP IN UZBEKISTAN AND METHODS OF USING NEW PEDAGOGICAL TECHNOLOGIES IN TEACHING - Tohirova Shohsanam (Researchparks Publishing, 2023)
This article discusses the condition of ESP in Uzbekistan. Moreover, it focuses on the main factors of teaching English for Specific Purposes (ESP) using new pedagogical technologies. The importance of using interactive methods and non-traditional approaches in teaching has been proved with the scientific facts and personal experience of the author.